Performance investigations on data protection algorithms in generalized multi protocol label switched optical networks - Monika; Singh, Simranjit; Wason, Amit (Scientific reports, 2023)
In future generation networks, data protection is a crucial necessity particularly when information is sent on a system. Network protection has three objectives known as discretion, reliability and accessibility. The most common procedure exploited to attain this ambition is encryption. The Generalized Multi Protocol Label Switched (GMPLS) optical networks are designed to survive Internet Protocol’s (IPʹs) unreliable delivery. In this paper, GMPLS network is proposed with random users and then the data protection algorithms have been analyzed on proposed GMPLS optical network. The various algorithms involve Rivest Shamir Adleman (RSA) algorithm and Advanced Encryption Standard (AES) algorithm. The considered algorithms are very popular but have not been implemented on GMPLS optical networks in the literature which shows the novelty of the presented work. The network performance is compared for these algorithms in terms of various parameters like blocking probability and latency. The results reveal that RSA reduces the blocking probability < 0.005 and latency < 0.007 ms. This shows that RSA gives better performance than AES algorithm and enhance the quality of service considering blocking probability, latency and overheads in GMPLS optical networks leading to enhanced data protection.